Rewiring immune evasion in liver metastases: WNT11 as a central node — a mini review - Wang, Xiaoling; Huang, Youcai; Luo, Tingting; Liu, Qinxian; Tian, Yu; Hu, Xiaoyu; Zheng, Yi; Fang, Shumin; Tu, Yanyang; Zhen, Haining; Guo, Yu (Frontiers in Oncology, 2025)
Liver metastasis (LM) poses a formidable barrier to effective immunotherapy, largely due to its uniquely immunosuppressive microenvironment and resistance to immune checkpoint blockade (ICB).Among emerging mechanisms, WNT11, a non-canonical WNT ligand, has been identified as a preclinical modulator of immune evasion in LM. Acting through a calcium-dependent CAMKII signaling pathway axis, WNT11 suppresses CD8+ T-cell recruitment via downregulation of chemokines such as CXCL10 and CCL4 and promotes M2-like macrophage polarization through IL17D induction. This dual mechanism contributes to the formation of an immune-excluded, tolerogenic niche that undermines the efficacy of anti-PD-1 therapies. Targeting the WNT11/CAMKII axis restores immune infiltration and sensitizes LM to ICB in preclinical models, highlighting a promising therapeutic strategy. Although no direct WNT11-targeted therapies are currently available, multiple pharmacological strategies targeting its proximal and downstream effectors—such as FZD/ROR, CAMKII, PKC/JNK/NFAT, and associated crosstalk pathways like TGF-β, IDO1, and myeloid axes—are under active exploration. Additionally, circulating WNT11 levels may also serve as a predictive biomarker for patient stratification and treatment monitoring. Despite challenges related to pathway complexity and tumor heterogeneity, this mini review synthesizes recent advances in understanding the WNT11-driven tumor-immune axis and proposes a translational roadmap for combination strategies to overcome ICB resistance in liver metastasis.